Influence of Social Support Network and Perceived Social Support on the Subjective Wellbeing of Mothers of Children With Autism Spectrum Disorder - Bi, Xiao-bin; He, Hui-zhong; Lin, Hai-ying; Fan, Xiao-zhuang (Frontiers in Psychology, 2022)
This study explored the relations between the social support network of mothers of children with autism spectrum disorder (ASD), perceived social support, and their subjective wellbeing. The participants were mothers of children with ASD in Shanghai. Their social support network structure was explored via the nomination method. Perceived social support was measured using the Revised Social Provisions Scale for Autism (R-SPS-A), and the mothers’ subjective wellbeing was assessed using the Index of Wellbeing, Index of General Affect. A significant correlation was observed between the subjective wellbeing of mothers of children with ASD and perceived social support. Meanwhile, perceived social support was significantly correlated with the effectiveness of overall social support. Finally, perceived social support was also significantly correlated with the network size of social support. Moreover, the effectiveness of social support was significantly associated with the network size of social support and was highly significantly associated with the degree of intimacy of social support. Furthermore, the network size of instrumental support has a significant influence on all perceived social support subdimensions. Overall, social support effectiveness plays an important role in the social support network mechanism on perceived social support and subjective wellbeing in China.